The evolutionary history of Shigella flexneri serotype 6 in Asia. Issue 12 (14th December 2021) - Mai, Si-Nguyen T.; Bodhidatta, Ladaporn; Turner, Paul; Wangchuk, Sonam; Ha Thanh, Tuyen; Voong Vinh, Phat; Pham, Duy Thanh; Rabaa, Maia A.; Thwaites, Guy E.; Thomson, Nicholas R.; Baker, Stephen; Chung The, Hao
Abstract : Shigella flexneri serotype 6 is an understudied cause of diarrhoeal diseases in developing countries, and has been proposed as one of the major targets for vaccine development against shigellosis. Despite being named as S. flexneri, Shigella flexneri serotype 6 is phylogenetically distinct from other S. flexneri serotypes and more closely related to S. boydii . This unique phylogenetic relationship and its low sampling frequency have hampered genomic research on this pathogen. Herein, by utilizing whole genome sequencing (WGS) and analyses of Shigella flexneri serotype 6 collected from epidemiological studies (1987–2013) in four Asian countries, we revealed its population structure and evolutionary history in the region. Phylogenetic analyses supported the delineation of Asian Shigella flexneri serotype 6 into two phylogenetic groups (PG-1 and −2). Notably, temporal phylogenetic approaches showed that extant Asian S. flexneri serotype 6 could be traced back to an inferred common ancestor arising in the 18 th century. The dominant lineage PG-1 likely emerged in the 1970s, which coincided with the times to most recent common ancestors (tMRCAs) inferred from other major Southeast Asian S. flexneri serotypes. Similar to other S. flexneri serotypes in the same period in Asia, genomic analyses showed that resistance to first-generation antimicrobials was widespread, while resistance to more recent first-line antimicrobials was rare. These data also showed a number of gene inactivation and gene loss events, particularly on genes related to metabolism and synthesis of cellular appendages, emphasizing the continuing role of reductive evolution in the adaptation of the pathogen to an intracellular lifestyle. Together, our findings reveal insights into the genomic evolution of the understudied Shigella flexneri serotype 6, providing a new piece in the puzzle of Shigella epidemiology and evolution.